(untitled) (Research, Society and Development, 2020)
Objective: The impact of the active videogame, with the aid of gamification, on the frequency of consumption of unhealthy foods among overweight or obese teenagers was evaluated. Methods: Controlled intervention study with two comparison groups (experimental and control), developed in two public schools in the city of Campina Grande - PB. The intervention was carried out with the aid of an exergame (XBOX 360), in the period of eight weeks, associated with gamification. The data were collected in both groups, before and after the intervention, namely: nutritional status, food (frequency of consumption of unhealthy foods), lifestyle and sociodemographic. The data were evaluated using the qui-square and McNemar test using SPSS 22.0, adopting a significance level of 5%. The study was approved by the Ethics Committee, REBEC and Clinical Trials. Results: Of the total, 76 teenagers completed the study. As for sex, 51.3% were female. Sedentary screen time was reported by 86.8% of teenagers and an inactive lifestyle by 34.2%. 52.6% were overweight and 68.5% had abdominal adiposity. In the comparison between the groups, there was no statistically significant difference regarding the frequency of consumption of unhealthy foods after the intervention. However, in the intra-group comparison, before and after the intervention, there was a reduction in the weekly frequency for the consumption of some foods. Conclusion: It was possible to verify that the use of active videogame as a PA practice tool, had an impact on the consumption of some unhealthy foods in the experimental group, such as chocolate, soft drink and popsicles.